Outage probability due to intercore crosstalk in weakly-coupled MCF systems with OOK signaling - Alves, T.; Rebola, J.; Cartaxo, A. (2019 Optical Fiber Communications Conference and Exhibition, OFC 2019 - Proceedings, 2019)
The outage induced by intercore-crosstalk in multicore-fiber systems employing on-offkeying signaling is theoretically and experimentally characterized. It is shown that a crosstalk level below -16 dB is required to obtain an outage probability below 10e-4